Long-distance dispersal in a recovering endangered shorebird population facilitates recolonization of historical nesting sites following decades of extirpation - Andrew David. Brown; Francesca Cuthbert; Alice Van Zoeren; Stephanie Schubel; Erica Nol (Journal of Field Ornithology, 2022)
After extirpation from most of the Great Lakes by the 1980s, the Piping Plover (Charadrius melodus circumcinctus) did not nest again outside Michigan until 1998. The number of Plovers breeding in the region has gradually increased, with nesting locations expanding from Michigan. We studied the pattern of dispersers recolonizing their historical range after near extirpation using data from individually identifiable banded birds. Objectives were to determine if: (1) the origin of the first recolonizing individuals was Michigan; (2) dispersers remained within the Great Lakes population boundaries; (3) colonizing individuals were mainly natal dispersers; and (4) dispersal distances differed between the sexes and between natal and breeding dispersers. Finally, we tested the effects of time (year), yearly average Great Lakes water-level anomalies, and number of breeding pairs per year in Michigan on the rate of colonization outside Michigan. Plovers recolonized the Great Lakes primarily via recruits from Michigan. Additionally, six individuals were recorded leaving the Great Lakes and colonizing locations within Northern Great Plains and Atlantic Coast population boundaries. Colonizers dispersed on average 489.0 ± 55.0 km with no significant differences in distances between males and females or between natal and breeding dispersal events. No significant effect was found of water-level anomalies or number of breeding pairs in Michigan on the number of colonizers, but there was a positive effect of year. Our findings demonstrate that birds will return to sites unused for decades if the habitat is still suitable. The results also identify key locations that can support the continued growth of the endangered Great Lakes Piping Plover population as it increases toward recovery goals.